EFECTIVITIES OF HEALTH EDUCATION WITH THE DEMONSTRATION METHOD AND THE LECTURES METHOD OF PRIMIPARA MOTHER’S KNOWLEDGE ABOUT BREAST CARE IN THE REGION OF SOCIAL HEALTH CENTER KAYUMAS - Sabekti Utami Safitri; Witriyani .; Erlina Hermawati (STIKES DUTAGAMA KLATEN, 2017)
Background: Breast care is an act of caring for breast lactation primarily to launch a spending of breast milk. At the time of parturition breast infection can occur, especially at the mother of primipara parturition. Infection occurs through wound on the nipple and the blood circulation. Objective: The purpose of the research to find the effectivities of health education with the demonstration method and the method lectures of primipara mother’s knowledge about breast care in the region of social health center Kayumas. Methods: This research using quasy experimental design with non equivalent control group and using pretest-posttest control group design. The population of this research was the mother of primipara, with sample as many as 30 respondents. Data analysis Wilcoxon Match Pair Test. Results: Based on results of a Wilcoxon test indicates that the control group with p value 0.317 > p value 0.05 mean knowledge there is no difference. A p value of 0.025 < p value 0.05 mean so there is a difference knowledge on respondent groups were given health education methods lectures, while the p value of 0.014 < p value 0.05 mean so there is a difference knowledge on the group that was given a health education demostration method. After health education with the demonstration method and lectures method, with the results of the p value of 0.014 compared with p value 0.025 means show that there is a difference between the health education by the demonstration method and the lectures method p value 0.014 < 0.025. Conclusion: Health education using demonstration method more effective to increase of primipara mother’s knowledge about breast care in the region of social health center Kayumas.